2019
DOI: 10.1088/1361-6463/ab51f3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effects and transport mechanisms of iron vapour in tungsten inert-gas welding in argon

Abstract: Tungsten inert-gas (TIG) welding uses an electric arc between a tungsten cathode and a metal anode to partially melt the anode workpiece, forming a weld pool. Metal vapour emanating from the weld pool has important effects on the arc welding process. An axisymmetric computational model of the arc and weld pool is used to examine the transport and influence of iron vapour on an argon arc plasma. In contrast to previous studies that use approximate and incomplete treatments of diffusion, the present model incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
(76 reference statements)
0
7
0
1
Order By: Relevance
“….溶 接アークプラズマに対して発光分光分析を適用することで, 近年では重ねすみ肉アーク溶接時のガスシールド性 16) やガ スメタルアーク溶接現象に与えるシールドガス組成の影響 17) ,ティグ溶接中の金属蒸気輸送およびそれに伴う電極消耗 メカニズム [18][19][20][21][22][23][24] Table 6 Ionization energies of cerium and thorium 31) .…”
unclassified
“….溶 接アークプラズマに対して発光分光分析を適用することで, 近年では重ねすみ肉アーク溶接時のガスシールド性 16) やガ スメタルアーク溶接現象に与えるシールドガス組成の影響 17) ,ティグ溶接中の金属蒸気輸送およびそれに伴う電極消耗 メカニズム [18][19][20][21][22][23][24] Table 6 Ionization energies of cerium and thorium 31) .…”
unclassified
“…However, that effect was neglected in the present computation. Recent studies conducted by computation [ 87 , 88 ] and experimentation [ 89 , 90 ] have demonstrated that ion transport by cataphoresis affected the material vapor distribution in and around plasma.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as depicted in Figure 3, when pure chromium was used, the electrode tip emitted strong light, which suggests that the temperature of the electrode contaminated with chromium vapour was increased. Moreover, results of earlier studies clarified that the metal vapour generated from the weld pool surface was transported to near the electrode tip during argon TIG welding [18, 19]. Therefore, a concern exists that the electrode is similarly contaminated during argon TIG welding.…”
Section: Discussionmentioning
confidence: 99%